The interactive effect of depressant type and dosage with frother dosage in the flotation of a PGE ore - Dhliwayo, Evelyn Chengetanai (Department of Chemical Engineering, 2014)
The valuable components of the platinum group element (PGE) bearing ores of the Bushveld complex in South Africa constitute between 1 % and as little as 0.1 % of the total mass. In the processing of these ores by flotation, the naturally hydrophobic talc minerals cause over stable froths. The drainage of liquid and entrained particles is reduced thus the recovery of other gangue minerals by entrainment increases and grade decreases. In the rougher float depressants are added to produce a manageable froth and improve the grade by reducing the overall amount of the naturally floating gangue in the concentrates. Depending on dosage, depressants may also affect the recovery of the valuable minerals in the ore positively by slime cleaning or negatively by depression. Depression of stabilising gangue minerals such as talc decreases the froth stability and may also affect the recovery of valuables. Frothers are added to flotation systems to create stable froths. They increase the water layer around bubbles and the carrying capacity of the froth and thus recovery by entrainment. The drainage of entrained particles from the froth may be further increased by increasing the froth depth. This study investigated the interactive effects of depressant dosage and type, frother dosage and froth depth on the recovery and grade of copper and nickel sulphides, recovery of water, floatable and entrained gangue in the flotation of a Merensky ore. Since it is known that water recovery is closely related to froth stability it was used to infer froth stability in this study. Two types of depressants carboxymethyl cellulose (CMC) and guar gums which are usually used in the flotation of PGE bearing ores were used. The frother was Dow 250. Results showed that increasing either guar or CMC dosages from 50 to 100 g/t enhanced the recovery of copper and nickel sulphides. This was attributed to the slime cleaning action of the depressants and their stabilising effects. A further increase of dosage to 300 g/t decreased the recovery of copper and nickel indicating that depression of sulphides occurs at high depressant dosages. Both the use of guar and CMC depressants reduced the recovery of floatable gangue with increasing dosage as expected. The guar depressant showed greater depression ability at 50 g/t dosage than the CMC depressant while the CMC was more effective at 100 and 300 g/t dosage. Reduction of water recovery by the CMC depressant was greater than that of the guar depressant indicating that the CMC depressant had greater destabilising effects on the froth. It is known that the CMC depressant has a strong negative charge while the guar depressant is only slightly charged. The guar depressant may have caused aggregation of particles which has less destabilising effects than the dispersed particles in the presence of the CMC depressant. The froth recoveries showed that the effects of depressant and frother dosages counteract each other and that the decrease in the recovery of copper and nickel sulphides obtained at higher depressant dosages can be reversed by increasing frother dosage. However although increased frother dosage readily reverses the depressant effects, an increase of water and recovery by entrainment reduces the grade. The effect of depressant dosage increase on the water and froth stability is small in comparison to the effect of increased frother dosage. Thus for the levels tested the benefit of improved grade obtained by depressant addition would be lost. The increase of froth depth to reduce entrainment resulted in a reduction of the recoveries of the valuable minerals but with the desired increase in grade. Smaller increments of frother dosage are required to produce effective reversal of depressant effects on the recovery of valuable minerals to achieve a good overall flotation performance.